2000
DOI: 10.1007/bf02490445
|View full text |Cite
|
Sign up to set email alerts
|

Profiling propolis flavonoids by means of micellar electrokinetic capillary chromatography, capillary gas chromatography and bactericidal action

Abstract: SummaryThere is no proportional correlation between increasing organic solvent polarity from hexane to methanol and the extractability of propolis solids by the solvents or the bactericidal action of the propolis extracts obtained. Hexane (17.7%) and chloroform (62.]. %) were the poorest and the best extractants, respectiveI,F for propolis solids. The antibiotic activity of the extracts against Staphylococcus strains decreased in the order hexane > ethanol > methanol. Different capillary GC profiles were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…As a consequence, a propolis extract very rich in phenolic acids was investigated [13]. By performing a MEKC separation of propolis alcoholic extracts, the same authors [13] and Fontana et al [14] found P, Ch, and G to be the flavonoids at the highest concentration, in good agreement with the present study. Furthermore, Bankova et al [16,17] also found that P, G, and Ch are the main flavonoids in other propolis samples.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As a consequence, a propolis extract very rich in phenolic acids was investigated [13]. By performing a MEKC separation of propolis alcoholic extracts, the same authors [13] and Fontana et al [14] found P, Ch, and G to be the flavonoids at the highest concentration, in good agreement with the present study. Furthermore, Bankova et al [16,17] also found that P, G, and Ch are the main flavonoids in other propolis samples.…”
Section: Resultssupporting
confidence: 90%
“…Due to its several advantages, such as the rapidity of the method, the small sample amounts required, and an extremely limited solvent waste, capillary electrophoresis (CE) has gained widespread interest as a favorable technique for the determination of pharmacologically interesting compounds in biological matrices, such as plants [6], leaves and flowers [7], herb medicines [8], tobacco [9], honey [10], tea [11], wine [12], human plasma, and urine. However, very few studies have reported on the characterization of flavonoids and phenolic acids from propolis by CE [13,14]. This paper aims to gain new insight into the qualitative and quantitative separation of the polyphenolic component of propolis preparations in the form of ethanolic, aqueous-ethanolic, and aqueous-glycolic extracts, usually used for commercial pharmaceutical preparations, by means of the capillary zone electrophoresis (CZE) technique.…”
Section: Introductionmentioning
confidence: 99%
“…-P ropolis is ac omplex phytochemical mixture and has been analyzed (after dissolvinga nd/or preparative steps)b yv arious methodologies, e.g., HPLC with different detectors [1 -3], GC/MS with or without derivatization procedure [4] [5],H P-TLC [6], micellar electrokinetic capillary chromatography [7], or NMR [8]. In addition, UV/VIS assays have been applied, e.g., to monitor the formation of AlCl 3 complexes for the quantitative determination of flavones and flavonols [9], the 2,4-dinitrophenylhydrazinem ethodf or flavanones [9], or the FolinÀCiocalteu method for the quantification of the total phenol (TP) content [10].…”
mentioning
confidence: 99%
“…Thus, the use of a high electrolyte concentration buffer along with a medium SDS concentration and the addition of a small proportion of methanol drawn to the most favourable combination [57]. Honey and other related products like propolis have been also widely studied using both, CZE [58,59] and MEKC [60][61][62]. One of the main flavonoids found in propolis is rutin.…”
Section: Other Flavonoidsmentioning
confidence: 99%